PRESERVING VALUES, UPHOLDING SHARIA: THE ROLE OF LAMAR KABIN IN MADURESE MARRIAGE TRADITION WITHIN THE FRAMEWORK OF EDUCATION AND RELIGION - A, Maimunah; Kurniawan, Syamsul (The Pontianak State Institute of Islamic Studies, 2025)
This article examines the practice of Lamar Kabin within the Madurese marriage tradition in Pontianak City, focusing on its cultural and religious educational dimensions. Lamar Kabin is understood not merely as a customary ritual but as a vehicle for imparting moral and spiritual values internalized within the Madurese community's habitus, integrating Islamic teachings and local wisdom. The study employs a phenomenological approach, utilizing participatory observation and in-depth interviews, and analyzes the data through Pierre Bourdieu's theory of habitus and Clifford Geertz's symbolic systems. Findings reveal that the Lamar Kabin tradition remains relevant as a process of social and religious learning and a means of cultural preservation amid modernization and globalization. This research underscores the vital role of tradition in fostering spiritual and cultural values adaptively and sustainably within urban Madurese society.